Product Differentiation Strategy in Achieving Competitive Advantage of CV Tirta Emas - Sari, Cica Permata; Nugraha, Alifian (INOVATOR, 2024)
Differentiation strategy is an effort made by the company by providing a difference between it products and products the market. Business have unique or different characteristics so that they are easily recognized by the public. This research aims to analize the product differentiation strategy carried out in achieving competitive advantage. This research, the author uses the theory stated by Feranita that there are six factors that can be done in carrying out a differentiation strategy to achieve competitive advantage. Excellenc can be measured by the uniqueness, quality and selling price of the product. The method applied is the descriptive qualitative case study method to generate data from the competent source person. The data collection is carried out by conducting observation techniques, interviews and documentation. The essence of this research is to maintain the differentiation strategy that has been implemented in achieving competitive advantage of CV Tirta Emas.